Revisiting human resource roles in Malaysian public hospitals - Mas Idayu, Saidi (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2022)
Link to publisher's homepage at https://ijbt.unimap.edu.my